The Legal System Application Affect Factors in Preventing HIV / AIDS Transmission in Bali - Prima Maharani Putri; I.G.A.K. Rachmi Handayani; Hartono Hartono; Widodo Tresno Novianto (Universitas Muhammadiyah Purwokerto, 2021)
The issue of HIV/AIDS as a human rights issue in relation to public health has in principle become a topic of conversation in international public health law. In 1946, the World Health Organization (WHO) proclaimed that the highest success of a goal of public health standards was success in the treatment of HIV/AIDS as a fundamental issue of human rights. According to the last data of November 2019, Bali was ranked in the top five cases of HIV/AIDS with the number of PEOPLE with HIV/AIDS reaching 22,034 people. Of the number of cases nationally, Bali ranks number five after DKI Jakarta and West Java, even if reviewed from the average percentage compared to the population, Bali ranks in the top two nationally after Papua. The data when compared to the previous two years data is very different, where in 2017, Bali is still ranked sixth nationally. This article reviews Factors that affect the application of the legal system in preventing the transmission of HIV / AIDS in Bali Province. This research is a normative juridical research. Designed using the statute approach and conceptual approach. The results showed that Factors that affect the application of the legal system in preventing the transmission of HIV / AIDS in Bali Province are Multi-interpretation due to conflict norms in various cases about HIV/AIDS in Indonesia.. However, it needs Immediately formulate improvements or spelled out in the Regulation of the Governor of Bali to be more synergistic fundamentally in terms of HIV/AIDS Prevention, especially its transmission management and elimination namely to The Regional Regulation of Bali Province No. 6 of 2014 on Child Protection; Local Regulation of Bali Province No. 4/2019 on Indigenous Villages and Local Regulations of Bali Province No. 3/2006 on HIV/AIDS Prevention, as well as adjusting the Laws and Regulations on it.Keywords: HIV/AIDS, Legal System Application, Bali